Rekonstruksi Teori Penemuan Hukum di Era Digital Terkait Peran AI dalam Proses Peradilan (Studi Perbandingan Indonesia dan Tiongok) - Nur Rizkiah Hasanah; Irena Puspa Mega; Ivan Nurchalik (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The advancement of digital technology in the era of the Fourth Industrial Revolution has driven significant transformation across various sectors, including the field of law and judiciary. One of the key innovations emerging from this shift is the use of Artificial Intelligence (AI) to enhance efficiency and expedite case processing. This study aims to examine the implementation of AI in the Chinese judicial system, particularly through the innovation of the AI Prosecutor robot known as